Evidence of β-Cell Dedifferentiation in Human Type 2 Diabetes - Cinti, Francesca; Bouchi, Ryotaro; Kim-Muller, Ja Young; Ohmura, Yoshiaki; Sandoval, P. R.; Masini, Matilde; Marselli, Lorella; Suleiman, Mara; Ratner, Lloyd E.; Marchetti, Piero; Accili, Domenico (The journal of clinical endocrinology and metabolism, 2016)
Context:Diabetes is associated with a deficit of insulin-producing β-cells. Animal studies show that β-cells become dedifferentiated in diabetes, reverting to a progenitor-like stage, and partly converting to other endocrine cell types.Objective:To determine whether similar processes occur in human type 2 diabetes, we surveyed pancreatic islets from 15 diabetic and 15 nondiabetic organ donors.Design:We scored dedifferentiation using markers of endocrine lineage, β-cell-specific transcription factors, and a newly identified endocrine progenitor cell marker, aldehyde dehydrogenase 1A3.Results:By these criteria, dedifferentiated cells accounted for 31.9% of β-cells in type 2 diabetics vs 8.7% in controls, and for 16.8% vs 6.5% of all endocrine cells (P < .001). The number of aldehyde dehydrogenase 1A3-positive/hormone-negative cells was 3-fold higher in diabetics compared with controls. Moreover, β-cell-specific transcription factors were ectopically found in glucagon- and somatostatin-producing cells of diabetic subjects.Conclusions:The data support the view that pancreatic β-cells become dedifferentiated and convert to α- and δ-“like” cells in human type 2 diabetes. The findings should prompt a reassessment of goals in the prevention and treatment of β-cell dysfunction.